Persepsi Mahasiswa PGSD terhadap Mata Kuliah Olahraga Anak dalam Mempersiapkan Kompetensi Mengajar di Sekolah Dasar - Ahmad Rif'an Najih; Azhar Syarifuddin; Wulida Arina Najwa (STKIP AL HIKMAH SURABAYA, 2026)
The Children's Physical Education Course is one of the core courses designed to equip students of the Primary School Teacher Education Program (PGSD) with the competencies required to plan and implement physical education learning in elementary schools. This study aimed to describe PGSD students' perceptions of the Children's Physical Education Course in preparing their teaching competencies for elementary schools. A descriptive quantitative approach was employed involving PGSD students who had completed the course. Data were collected using a four-point Likert-scale questionnaire and analyzed descriptively using the mean score, Ideal Mean (Mi), and Ideal Standard Deviation (SDi). Interviews were conducted as supporting data to enrich the interpretation of the quantitative findings. The results revealed that students' perceptions of the course were categorized as good, with an average score of 80.67. The highest scores were obtained for the indicators of course benefits and content relevance, whereas teaching self-confidence and course relevance to the teaching profession received relatively lower scores. These findings indicate that the Children's Physical Education Course has positively contributed to preparing students' teaching competencies. However, strengthening practical teaching experiences and enhancing the relevance of course content to the professional demands of elementary school teachers remain necessary.